Perceived doctor-patient relationship, authentic leadership and organizational climate on physician burnout: job satisfaction as a mediator - Wenwen Liang; Jing Wang; Xiaoting Wang; Guimei Chen; Ren Chen; Jing Cheng (BMC Health Services Research)
Abstract Background This study aims to investigate the direct associations among perceived doctor-patient relationship, authentic leadership, organizational climate, and job burnout, as well as the indirect pathways through job satisfaction, with the aim of offering potential preventive strategies at the organizational level. Methods A total of 399 physicians from six tertiary hospitals in Anhui Province were enrolled by purposive sampling method. Structural equation modeling was performed to examine the proposed model. Results The average score of the participants' job burnout was 35.22 (SD: 12.14), and the burnout rate was found to be 55.7%. Perceived doctor-patient relationship, organizational climate directly influenced job burnout. Perceived doctor-patient relationship, authentic leadership and organizational climate also indirectly influenced burnout through job satisfaction. Conclusions The present study underscores the significant influence of the perceived doctor-patient relationship, authentic leadership and organizational climate in mitigating burnout, and further reveals that job satisfaction serves to alleviate burnout. It is crucial to emphasize the importance of both internal and external psychosocial and organizational environmental factors. Additionally, the study highlights the pivotal role of job satisfaction in influencing physician burnout.